The Fraud Tree and its Investigation in Audit - Mackevičius, Jonas; Kazlauskienė, Laimutė (Ekonomika, 2009)
The purpose of the present research paper is to introduce a new structure of the Fraud Tree and to suggest certain audit procedures possibly employed in examining its branches. For the purpose of the present paper the authors thereof have referred to the analysis of related research literature, also applied the information comparison and generalization methods. Fraud is being committed in every part of the world, and in every sphere of human activities. Often fraud leads to financial nightmare and collapse of major international corporations which cause spill-off after-effects not only upon corporations and their employees, but also upon other related businesses and organizations, governments and societies. In view of globalization of economy, increasingly dynamic and competitive business fraud has changed in character though has not downscaled in its scope. Today fraudsters elaborate their attempts making use of the most state-of-the-art science achievements and innovative technologies. This largely facilitates the growth of the “Fraud Tree” with its new branches ever springing up. The present article represents an attempt to investigate individual fraud cases and the groups of persons committing this kind of crime. A new concept of “Fraud Tree” has been introduced with the following basic branches: i) material misstatements in financial statements; ii) asset misappropriation; iii) corruption; iv) tax evasion; and v) others. Every branch on the Fraud Tree has several sub-branches, and significant efforts should be devoted in the course of audit to examine the scope, formation conditions of each such sub-branch. The present paper includes guidelines for the principal actions and procedures to be followed by an auditor in view of the risks related to misstatements in financial statements, asset misappropriation, corruption and tax evasion.
Keywords: fraud; Fraud Tree; fraud detection; investigation